Comparison of local versus spinal anaesthesia in inguinal hernia repair - Bhardwaj, Suraj; Sharma, Shuchi; Bhardwaj, Vatika; Lal, Roshan (International Surgery Journal, 2020)
Background: Inguinal hernioplasty remain one of the most commonly performed operations worldwide. Local anaesthesia can be a preferred method in day-case hernia surgeries. Present study was thus conducted to determine whether local anaesthetic technique is an acceptable alternative to spinal anaesthesia for hernia repair, especially with regards to operative conditions, postoperative pain relief and complications. Methods: This was a prospective randomized single blinded clinical study consisting of sixty patients conducted after the ethical committee clearance. The patients posted for tension free lichtenstein elective hernioplasty were allocated to either of two groups, group A (n=30) were given local anaesthesia and patients in group B (n=30) were given spinal anaesthesia. The operative and postoperative pain sore using visual analogue scale, duration of surgery and any other complications were recorded. Results: There was no demographic difference between the two groups. Time taken in local anesthesia was higher than spinal anesthesia. Intraoperative pain was higher in local anesthesia than spinal anesthesia. There was no difference in post-operative pain scores (p>0.05). Post-operative complications were more in spinal anesthesia group e.g. urinary retention, headache, etc. Conclusions: Local anesthesia can be another good choice for inguinal hernia repair owing to its advantages and less complications, but it can’t be confirmed that local anaesthesia is better than spinal anaesthesia. It can be reliably concluded that local anaesthesia can be a preferred method in day-case hernia surgeries owing to its advantages of ease of administration and less complications.